Optimasi Ekstraksi Teh Hijau Berdasarkan Kandungan Polifenol, Aktivitas Antioksidan dan Profil Sensori - Nurheni Sri Palupi; Dase Hunaefi; Nugraha Susanto (Jurnal Tanaman Industri dan Penyegar, 2021)
Green tea contains polyphenols which are known as sources of antioxidants and contribute to a bitter and astringent taste. Optimization of green tea extraction to obtain sensory profiles that are acceptable for consumers is important. The study aimed to produce an optimal green tea extraction process based on polyphenols content and antioxidant activity, a sensory profile of the basic solution of green tea based on consumer expectations and preferences, and the ideal profile of green tea. This research was conducted by PT. XYZ – Jakarta and Department of Food Science and Technology, Faculty of Agricultural Technology IPB University – Bogor, West Java from October 2020 to April 2021. This study used data experiments on RSM by CCD method and consumer perception testing using Check-All-That-Apply (CATA) method. The selection of consumer panelists and FGD participants was conducted in conjunction with the consumer survey.  Optimum condition of methode extraction of green tea based on RSM methode was temperature at 78,43 OC for 21 minutes. Total of polyphenols, antioxidant activity based on IC50, and preference score was 588,58 mg/kg – 750 mg/kg; 14,48μL – 27,03μL; and 4,0 – 5,2, respectively. Green tea extract profile based on consumers preferences had the following profile sensory: burned aroma, floral aroma, tobacco aroma, animalic aroma, umami test, green flavor, astringent aftertaste, straw-like aftertaste; emotional profile: peaceful, adventurous, calm and satisfied; and attribute profile: packaging design: cold color, illustrations image, images of people, combination, high quality and warm color.